2014
DOI: 10.1590/0037-8682-0013-2014
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and parasitic infections: similarities and opportunities for the development of new control tools

Abstract: Lifestyle similarities between parasites and cancer have inspired parasitologists to use approaches analogous to those used in oncology and to explore the interface between these fields. The similarities have not escaped the notice of oncologists. Cancer may be thought of as a developing species that behaves in a manner akin to parasites 1 . Both are autonomous and not subjected to regular signaling mechanisms, although they make use of signals and resources for their own benefit. In parasitology, research app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…In addition, studies have linked Cryptosporidium spp., among other parasites, to the development of cancer, inasmuch as it is believed that chronic inflammation of the intestinal tract due to the presence of the parasite could induce pathological disorders with adenocarcinoma genesis. Studies have also shown that even low doses of this protozoan may induce gastrointestinal neoplasia (Benamrouz et al, 2014;Oliveira, 2014). Nevertheless, this relationship has not been diagnosed in this study.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, studies have linked Cryptosporidium spp., among other parasites, to the development of cancer, inasmuch as it is believed that chronic inflammation of the intestinal tract due to the presence of the parasite could induce pathological disorders with adenocarcinoma genesis. Studies have also shown that even low doses of this protozoan may induce gastrointestinal neoplasia (Benamrouz et al, 2014;Oliveira, 2014). Nevertheless, this relationship has not been diagnosed in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Among them, in a typical rule, Acidibacillus and Nitrospira are two typical microorganisms that may contribute to the tumorigenesis of such cancer subtype and may participate in the distinction from other cancer subtypes. According to recent publications, these two microorganisms are identified in biological samples from patients with urothelial bladder carcinoma, indicating that both microorganisms are enriched in urothelial bladder carcinoma-associated tissues ( Oliveira, 2014 ; Weng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although bacteria and parasites are vastly different organisms, with many differences in their acquisition of resistance, there are several characteristics that share similarity e.g. between malaria, TB and HIV [25], and parasites and cancer cells [44,45]. These shared characteristics may serve as a viaduct offering unconventional but perhaps valid strategies for the field of antimalarial research in a "piggyback" approach.…”
Section: Resisting Resistance: New Innovationsmentioning
confidence: 99%